Analisis Bioakustik untuk Menguji Kemampuan Verbal Down Syndrome: Studi Kasus Peli dan Sutan di SLB Negeri 1 Padang - Rizki Ramadhani Harahap; Anita Angraini Lubis (Jurnal Hata Poda, 2022)
This research is aimed at describing the verbal competence of down syndrome in different age of Peli and Sutan based on bioacustic analysis by using spektogram Speech Analyzer. A objectives of the research are to analyze the competence in phonology and morphlogy and to identify the factors which affect the difference of verbal competence between P and S. This research is a case study of two students at SLB Negeri 1 Padang. Methods used to collect data are observation and analytics, session study, and preobservation. Participacy observation (SLC), non participatory observation (SBLC), recording, note,  taking recording by using speech analyzer, flash card, are the technique. In data analysis used articulator  to present the result of analysis is implemented fornal and informal method. The source of the data this research is oral data  which are taken from the patients of down syndrome said, they are P and S.  Based on the data analysis, the result of productivity competence of P based on bioacoustics analysis by using spektogram SA audacity and the research instrument in form of flash card (FC), it is in the range of 20,30 dB. While the result of productivity competence of S based on bioacoustics by using spectogram SA audacity and research instrument in the form of flash card (FC), it is in the range of 14,25 dB. P is able can understand the affixation usage outline of flash card (FC)  showed to him. There are 6 kinds of affixations  produced by P and 11 form by P. Different from S who has not  able to produce affixation at all, because syllable which has been able to produced tent to the end of the sylablle for every flash card which is show to S. The factors which influence the difference of verbal competence of DS in different age for P and S, they are disturbance of attention, memory interruption, disturbance of emotions and feelings, and psychological factor. Key words: verbal competence (fonology and morfology), Speech Analyzer, Down Syndrome.